Analisis Pendapatan Usaha Tani Kelapa di Kampung Kendahe I Kecamatan Kendahe Kabupaten Sangihe - Paulus Sasiang; Celsius Talumingan; Caroline B.D, Pakasi; Lorraine W. Th. Sondakh (COCOS, 2014)
ABSTRACTPaulus Sasiang. Coconut Farm Income Analysis at Kendahe I Village, Kendahe Sub District (Under the guidance of C. Talumingan as chairman, C. B. D. Pakasi and L. W. Th. Sondakh as members).The objective of this research is to determine the income of coconut farmers at Kendahe I Village Kendahe Sub District. This research uses the survey method. Data used is primary data and secondary data. Primary data obtained through direct interview by a list of questionnaire to the farmer, the secondary data obtained from the related institution.The data presented in tabular form and analyzed descriptively, to determine income uses FI = TR – TC formula, furthermore to determine if coconut farming giving benefits or not using R/C ratio formula.The result of this research showed that the average revenue coconut farming in Kendahe Village was Rp. 8.517.900, with an average cost Rp. 1.020.411, so that the average income received by farms Rp. 7.491.489, for 3 times harvest process. By considering based on the average area of farms owned land 1 ha, the average was Rp. 2.499.163. Based on R/C ratio calculation, The R/C was 8,35. Thus coconut farm in Kendahe village was benefits for farmers.